c - 9; 9; 9; 9 (b, 2011)
Articles on the life and works of Emajuddin Ahamed, educator and professor from Bangladesh; commemorative volume.
In Bengali; includes passages in English.
Keywords: Ahmed, Emajuddin; Educators -- Bangladesh -- Biography; College teachers -- Bangladesh -- Biography